2021
DOI: 10.1101/2021.03.17.435829
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

An efficient urine peptidomics workflow identifies chemically defined dietary gluten peptides from patients with celiac disease

Abstract: Celiac disease (CeD) is a common autoimmune disorder induced by consuming gluten proteins found in wheat, barley, and rye. Glutens resist breakdown by gastrointestinal proteases, ultimately resulting in peptides with chemical structures that elicit inflammation in patients with CeD. Despite well-established connections between digestion-resistant glutens and CeD, chemically defined, bioavailable peptides produced from dietary proteins have never been identified from humans in an unbiased manner. This is largel… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 60 publications
(116 reference statements)
0
2
0
Order By: Relevance
“…In fact, it was described that patients with CD may have a higher proteolytic activity in the intestine leading to a gluten reduction in feces in comparison to healthy subjects and first-degree relatives on normal diet [ 37 ]. Moreover, a recent study confirmed that patients with CD consuming wheat excreted in urine a significantly higher diversity of gluten-derived peptides than healthy subjects, however differences the healing of the intestinal epithelia between patients with CD were not contemplated [ 28 ]. Thus, since the test for GIP detection in urine is intended for use by people suffering from CD and gluten-related disorders, future studies with these populations with similar gluten consumptions will confirm the compatibility of our results for the definition of clinical practice guidelines for the application of GIP in the monitoring of GFD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, it was described that patients with CD may have a higher proteolytic activity in the intestine leading to a gluten reduction in feces in comparison to healthy subjects and first-degree relatives on normal diet [ 37 ]. Moreover, a recent study confirmed that patients with CD consuming wheat excreted in urine a significantly higher diversity of gluten-derived peptides than healthy subjects, however differences the healing of the intestinal epithelia between patients with CD were not contemplated [ 28 ]. Thus, since the test for GIP detection in urine is intended for use by people suffering from CD and gluten-related disorders, future studies with these populations with similar gluten consumptions will confirm the compatibility of our results for the definition of clinical practice guidelines for the application of GIP in the monitoring of GFD.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it has been described that a fraction of longer peptides resistant to the action of the peptidases can also cross the basolateral membrane of the enterocytes and reach portal circulation [ 21 ]. Several authors have reported the detection of GIP in the urine of patients with CD and healthy individuals using mass spectrometry and antibody-based methods [ 11 , 13 , 23 , 24 , 25 , 26 , 27 , 28 ]. Thus, they demonstrated that gluten-derived peptides enter the kidneys, and after the ultrafiltration process they are partially or totally excreted in the urine.…”
Section: Introductionmentioning
confidence: 99%